Second language learners’ reflections on the effectiveness of dictogloss: A multi-sectional, multi-level analysis - Gallego, Muriel (Studies in Second Language Learning and Teaching, 2014)
Despite the extensive research conducted regarding Focus on Form instruction, no conclusive results have been provided concerning (a) the issue of which techniques contribute most effectively to L2 acquisition, and b) at which level of proficiency those techniques should be implemented for best results. Dictogloss, one of these techniques, has been proven to be effective (Fortune, 2005; Kowal & Swain, 1994; Malmqvist, 2005; Nabei, 1996; Swain, 1998). While previous studies evaluating dictogloss explored feedback opportunities and the amount and type of language related episodes produced, fewer studies have reported on the effectiveness and its applicability according to proficiency level (Fortune, 2005; García Mayo, 2002) and none have explored learners’ conceptions about the task. Therefore, this study seeks to determine which proficiency level might be most appropriate for the implementation of dictogloss and to gather learners’ opinions regarding its usefulness and effectiveness. A total of 497 participants enrolled in novice-mid (N = 275) and advanced-low (N = 222) levels took part in the study. All participants engaged in two dictogloss tasks and completed a survey afterwards. Overall, results indicate that dictogloss was better received by advanced-low level students and that most students found it both useful and effective for learning.